Music therapy assessment : theory, research and application - Jacobsen, Stine Lindahl; Waldon, Eric G.; Gattino, Gustavo Schulze; Wheeler, Barbara L. (Jessica Kingsley Publishers, 2018)
This is an anthology of the latest research into assessment methods in music therapy. Based on the findings of members of the International Music Therapy Assessment Consortium (IMTAC), it covers issues such as the standardisation of robust assessment tools, the assessment models currently in use, and how to implement them in a clinical setting.